Perceptions of public university accounting graduates on skills necessary for workplace / Mustafa Mohd Hanefah and Samihah Hj. Ismail - Mohd Hanefah, Mustafa; Ismail, Samihah (Faculty of Accountancy, 2003)
Many researchers have debated the relevance of accounting curriculum to the employers in the U S and other developed countries Accounting graduates are said to lack various skills that are important in today's job market Among them are technological skills, oral and communication skills, and professional skills This phenomenon is not only common in developed countries, but also in the developing countries like Malaysia In Malaysia, graduates from local universities and colleges are facing unemployment due to the lack of such skills Although the Malaysian economy is performing better than other countries in this region, yet the unemployment rate among graduates is still high.